Navigating Organizational Change In Streaming Platforms: A Systematic Literature Review - Rachmansyah, Arief; El Khaldi, Malika (Universitas Indonesia Membangun (Inaba), 2025)
Despite the rapid growth and disruption introduced by streaming platforms in the media industry, little is known about how these organizations experience and manage internal change. Organizational change in this context is driven by evolving technologies, audience behaviors, and competitive dynamics. To better understand how streaming platforms navigate such change, a systematic literature review is conducted. We categorize existing research into major themes, including strategic adaptation, structural transformation, and innovation capabilities. We analyze the core characteristics of organizational change within streaming services, discuss theoretical and practical challenges, and highlight implications for both scholars and industry leaders. Finally, we propose future research directions to deepen our understanding of change management in digital platform environments.